Comprehensive characterization of formation rock for tight oil exploitation - Kang, Hao; Zhou, Xinyu; Gao, Jian; Zhang, Chunxiang (Frontiers in Energy Research, 2022)
Although it is generally very difficult to supplement flow energy into the tight oil reservoir, there is still good prospect for enhanced oil and gas recovery in this area due to its large proportion of hydrocarbon reserves. However, due to the sensitivity of tight oil reservoir to formation pressure, the porosity and permeability of the reservoir will change greatly with the change of formation pressure in the process oil development, which has a complex impact on dynamic analysis, productivity evaluation and later adjustment of potential stimulation measures. This study mainly focus on the characterization of tight formation rock in the Northwest part of China. In order to get a visual impression of the reservoir core, some routine tests were firstly carried out. After that, porosity and permeability are tested under overburden pressure conditions. Studies show that overburden porosity and permeability will decrease but total decrease percentage will increase with the increase of net effective overburden pressure. The decrease percentage of permeability is much higher compared with that of porosity decrease percentage under overburden pressures. When the net effective overburden pressure is larger than 10 MPa, the decrease of overburden porosity will become relatively small. At the same time, when the net effective overburden pressure is larger than 15 MPa, the decrease of overburden permeability will become relatively small. Taking the pressure-increasing process and the pressure-decreasing process as a whole: the permeability cannot recover to the initial level when overburden pressure is the same as previous round because certain permeability is permanently damaged in the process. At the same time, when the net effective overburden pressure increased to a higher level, the permeability damaged will become relatively smaller. These experiments compose of a comprehensive characterization of formation rock and are of great significance to accurately understand the reservoir damage in the process of tight oil development and reasonably evaluate the productivity of oil producers.